2002
DOI: 10.1093/ps/81.6.755
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feeding the direct-fed microbial, primalac, on growth parameters and egg production in single comb white leghorn hens

Abstract: Two commercial strains of Single Comb White Leghorn hens, HyLine W-36 and DeKalb XL, were reared separately as pullet flocks in an enclosed, environmentally controlled brood-grow house with three banks of quad-deck cages (310 cm2 per bird). There were 1,800 hens of each strain, which were divided into two groups, control feed and a direct-fed microbial (DFM) feed treatment. During the pullet-rearing phase to 18 wk of age, the DeKalb birds had greater parameters of growth and overall feed cost than the HyLine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 16 publications
4
27
0
Order By: Relevance
“…Similar studies reported a significant improvement of egg production in hens fed a mixed culture of probiotics, such as Lactobacillus acidophilus and Lactobacillus casei (Tortuero & Fernandez, 1995), L. acidophilus alone , Pediococcus acidilactici (Mikulski et al, 2012), Bacillus subtilis (Xu et al 2006;Abdelqader et al 2013), Propionibacterium jensenii (Luo et al, 2010), and Saccharomyces cerevisiae (Yalçin et al, 2010). Significant improvements in egg weight and eggshell quality were also obtained in hens fed diets supplemented with a mixture of Lactobacillus cultures (Davis & Anderson, 2002;Kalavathy et al, 2009).…”
Section: Effects Of Kluyveromyces Marxianus Isolated From Tibetan Musmentioning
confidence: 83%
See 1 more Smart Citation
“…Similar studies reported a significant improvement of egg production in hens fed a mixed culture of probiotics, such as Lactobacillus acidophilus and Lactobacillus casei (Tortuero & Fernandez, 1995), L. acidophilus alone , Pediococcus acidilactici (Mikulski et al, 2012), Bacillus subtilis (Xu et al 2006;Abdelqader et al 2013), Propionibacterium jensenii (Luo et al, 2010), and Saccharomyces cerevisiae (Yalçin et al, 2010). Significant improvements in egg weight and eggshell quality were also obtained in hens fed diets supplemented with a mixture of Lactobacillus cultures (Davis & Anderson, 2002;Kalavathy et al, 2009).…”
Section: Effects Of Kluyveromyces Marxianus Isolated From Tibetan Musmentioning
confidence: 83%
“…In recent years, there has been an increasing number of reports documenting the use of various yeast strains and yeast products, such as inactive dried yeast, yeast culture, whey yeast, selenium yeast, chromium yeast and yeast cell walls, in the diets of laying hens. The inclusion of yeast in layer diets was shown to change egg production (Davis & Anderson, 2002), cholesterol content of the egg yolk (Yousefi & Karkoodi, 2007;Yalçin et al, 2008a), intestinal health of the hens (Yalçin et al, 2010;Lensing et al, 2012), egg quality (Utterback et al, 2005;Yalçin et al, 2008a, b;Yalçin et al, 2009;Yalçin et al, 2010), and egg fat content (Savage et al, 1985;Hosseini, 2011), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the beneficial effect of PrimaLac (Lactobacillus acidophilus, Lactobacillus casei, Enterococcus faecium and Bifidobacterium bifidium) on growth parameters and egg production of laying hens was reported (Davis & Anderson, 2002), and the present study was designed to evaluate the effects of PrimaLac on performance (feed intake, FCR, mortality rate) of broiler chickens and on their antibody responses to routine vaccination with live NDV and infectious bursal disease virus vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…A combined mix culture of Lactobacillus acidophilus, L. Casei, Bifidobacterium thermophilus and Enterococcus faecium enhanced egg size and lowered feed cost in laying hens. 238 Moreover, Bifidobacterium thermophilus and Enterococcus faecium improved egg production and quality. 239 The use of Enterococci as probiotics is somewhat controversial in humans, but in chickens prolonged feeding with E. Faecium based probiotics increased egg laying intensity and feed conversion efficiency.…”
Section: -236mentioning
confidence: 99%